Construimos prototipos para cuidar el medio ambiente a través del reciclaje con alumnos de 1° grado de la I.E. 80937- Canibamba Alto – Usquil - 2019 - Angulo Enriquez, Azucena Charito (2021)
The present work of professional sufficiency is based on research action class session design with competence: Designs and builds technological solutions to solve problems in your environment. Your environment and performance: Perform the procedure for implementing your solution alternative and test until it works. Use unconventional units of measurement and test materials to help you build your solution alternative, select instruments and tools to help you craft it, meeting safety standards. Moreover, this session is based on the approach to research and scientific and technological literacy. Scientific research from school involves students building and rebuilding their scientific and technological knowledge based on their desire to know and understand the world around them and the pleasure of learning from the questioning of it. It also involves a reflection on the processes that are carried out during the research, in order to understand science and technology as a process and human product that is built collectively. Scientific and technological literacy means that students use knowledge in their daily lives to understand the world around them, how to do and think about science, in such a way as to guarantee their right to access training that allows them to function as responsible, critical and autonomous citizens in the face of personal or public situations that influence your quality of life and the environment in your community or country.